SeqSNP-based genic markers reveal genetic architecture and candidate genes for low nitrogen tolerance in tropical maize inbred lines - Abu, Pearl; Badu-Apraku, Baffour; Ifie, Beatrice Elohor; Eleblu, John Saviour Yaw; Ehemba, Georgina Lala; Tongoona, Pangirayi B.; Offei, Samuel Kwame (Frontiers in Plant Science, 2025)
Maize production in sub-Saharan Africa (SSA) faces significant challenges due to low soil nitrogen. To enhance breeding efficiency for low nitrogen tolerance, identifying quantitative trait loci (QTLs) in tropical germplasm is crucial to facilitate marker-assisted selection (MAS). In this study, gene targeting markers (GTM) derived from sequence-based single nucleotide polymorphisms (SeqSNP) were utilized to analyse the population structure and identify potential candidate genes associated with tolerance to low nitrogen. A total of 150 extra-early quality protein maize (QPM) inbred lines were assessed under both low (LN) and high (HN) nitrogen, followed by genotyping with 2,500 SeqSNPs targeting genes previously reported for LN tolerance-related traits. Population structure analysis revealed six sub-populations. Association mapping analysis revealed 15 significant single nucleotide polymorphisms (SNPs) linked to several key traits. Specifically, two SNPs each were associated with the low nitrogen base index (LNBI), which combines grain yield with other agronomic traits under low nitrogen, and the low nitrogen tolerance index (LNTI), a measure of grain yield performance in high nitrogen environments relative to low nitrogen environments. Additionally, one and ten SNPs were identified for grain yield under low and high nitrogen conditions, respectively. The two SNPs associated with LNTI were found to co-localize a potential gene hotspot, GRMZM2G077863, which belongs to the GDSL esterase/lipase gene family and is highly expressed in the roots of young seedlings six days after planting and during tassel meiosis prior to flowering. Additionally, several other putative genes were identified across different chromosomes: GRMZM2G026137 and GRMZM2G004459 on chromosome 1, GRMZM2G111809 on chromosome 2, GRMZM2G380319 on chromosome 3, GRMZM2G442057 and GRMZM2G080314 on chromosome 6, GRMZM2G011213 and GRMZM2G090928 on chromosome 8, and GRMZM2G338056 and GRMZM2G150598 on chromosome 9. The genes are involved in several functions including normal growth, tassel meiosis, root architecture, cell proliferation, cell growth, reproduction, and post-embryonic development. We report PZE-103012466, a marker co-localizing GRMZM2G380319, which was previously found to be associated with root elongation, as a useful marker for breeding low soil nitrogen tolerance in tropical germplasm. The validation of these markers and candidate genes in other populations could make them useful for MAS in breeding for nitrogen tolerance.